Will oscillating wave surge converters survive tsunamis? - O'Brien, Laura; Christodoulides, Paul; Renzi, Emiliano; Stefanakis, Themistoklis S.; Dias, Frederic (My University, 2015)
With an increasing emphasis on renewable energy resources, wave power technology is becoming one of the realistic solutions. However, the 2011 tsunami in Japan was a harsh reminder of the ferocity of the ocean. It is known that tsunamis are nearly undetectable in the open ocean but as the wave approaches the shore its energy is compressed, creating large destructive waves. The question posed here is whether an oscillating wave surge converter (OWSC) could withstand the force of an incoming tsunami. Several tools are used to provide an answer: an analytical 3D model developed within the framework of linear theory, a numerical model based on the non-linear shallow water equations and empirical formulas. Numerical results show that run-up and draw-down can be amplified under some circumstances, leading to an OWSC lying on dry ground!
Keywords: Oscillating wave surge converter; Tsunami; Wave energy converter; Wave loading; Wave-structure interaction